2015
DOI: 10.1093/molbev/msv070
|View full text |Cite
|
Sign up to set email alerts
|

Centromeres Off the Hook: Massive Changes in Centromere Size and Structure Following Duplication ofCenH3Gene inFabeaeSpecies

Abstract: In most eukaryotes, centromere is determined by the presence of the centromere-specific histone variant CenH3. Two types of chromosome morphology are generally recognized with respect to centromere organization. Monocentric chromosomes possess a single CenH3-containing domain in primary constriction, whereas holocentric chromosomes lack the primary constriction and display dispersed distribution of CenH3. Recently, metapolycentric chromosomes have been reported in Pisum sativum, representing an intermediate ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 88 publications
3
106
0
Order By: Relevance
“…CENH3 and centromereic repeats often show parallel evolution (Henikoff et al, 2001). Even diplod species such as A. halleri and A. lyrata (Kawabe et al, 2006), Pisum, Lathyrus (Neumann et al, 2015), and barley (Sanei et al, 2011), which possess complex centromeres and different kinds of centromeric satellite repeats show two copies of CENH3 . B. juncea is an allotetraploid and has five different kinds of centromeric satellite repeats (CentBr1, CentBr2, TR238, TR805, pBNBH35) (Lim et al, 2007; Koo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CENH3 and centromereic repeats often show parallel evolution (Henikoff et al, 2001). Even diplod species such as A. halleri and A. lyrata (Kawabe et al, 2006), Pisum, Lathyrus (Neumann et al, 2015), and barley (Sanei et al, 2011), which possess complex centromeres and different kinds of centromeric satellite repeats show two copies of CENH3 . B. juncea is an allotetraploid and has five different kinds of centromeric satellite repeats (CentBr1, CentBr2, TR238, TR805, pBNBH35) (Lim et al, 2007; Koo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…B. juncea is an allotetraploid and has five different kinds of centromeric satellite repeats (CentBr1, CentBr2, TR238, TR805, pBNBH35) (Lim et al, 2007; Koo et al, 2011). Diversity of centromeric repeats is a feature of B. rapa (Lim et al, 2007) and pea (Neumann et al, 2015) and in both these species, isoforms of CENH3 are found. In B. juncea, B. rapa -like CENH3 transcripts were more abundant than B. nigra -like transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…& W.C. Gregory, 1994) and Arachis correntina ((Burkart) Krapov. & W.C. Gregory, 1994) all belonging to the section Arachis (Fernández and Krapovickas 1994), and of other genera such as Antirrhinum majus (Linneaus, 1753), Allium sphaerocephalum (Crome ex Schltdl, 1824) (Lima De Faria 1956), Libocedrus chilensis (Endlicher, 1847) (Hunziker 1961), Pisum (Linneaus, 1753) and Lathyrus (Linnaeus, 1753) (Neumann et al 2015). Just recently, Neumann et al (2015) have classified this type of centromere as ‘intermediate’ between the two types of centromeres, monocentric and holocentric, and having an organization characterized by multiple Cen-H3 domains.…”
Section: Resultsmentioning
confidence: 99%
“…Diploid cereals like rice and maize have single copy of CENH3, while barley has two copies of CENH3 gene (Sanei et al 2011). Similarly, in the Leguminaceae family, Vicia faba and Lens culinaris have single copy of CENH3 while Pisum sativum and Lathyrus sativus have two copies of CENH3 (Neumann et al 2015).…”
Section: Copy Number and Splice Variants Of Cenh3mentioning
confidence: 99%